Proposal resubmission of VO #09 & 010 for steel structure works of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding proposal resubmission of VO #09 & 010 for steel structure works of BRAC University new campus project.